Performance determinants, running energetics and spatiotemporal gait parameters during a treadmill ultramarathon - Christopher C. F. Howe; Nicola Swann; Owen Spendiff; Anna Kosciuk; Elizabeth K. L. Pummell; Hannah J. Moir (European Journal of Applied Physiology, 2021)
Purpose The objective of this study was to investigate the changes in metabolic variables, running energetics and spatiotemporal gait parameters during an 80.5 km treadmill ultramarathon and establish which key predictive variables best determine ultramarathon performance. Methods Twelve participants (9 male and 3 female, age 34 ± 7 years, and maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max ) 60.4 ± 5.8 ml·kg −1 ·min −1 ) completed an 80.5 km time trial on a motorised treadmill in the fastest possible time. Metabolic variables: oxygen consumption ( $$\dot{V}$$ V ˙ O 2 ), carbon dioxide production ( $$\dot{V}$$ V ˙ CO 2 ) and pulmonary ventilation ( $$\dot{V}$$ V ˙ E ) were measured via indirect calorimetry every 16.1 km at a controlled speed of 8 km·h −1 and used to calculate respiratory exchange ratio (RER), the energy cost of running (Cr) and fractional utilisation of $$\dot{V}$$ V ˙ O 2max ( F ). Spatiotemporal gait parameters: stride length (SL) and cadence (SPM) were calculated via tri-axial accelerometery. Results Trial completion time was 09:00:18 ± 01:14:07 (hh:mm:ss). There were significant increases in $$\dot{V}$$ V ˙ O 2 , Cr, F , $$\dot{V}$$ V ˙ E and heart rate (HR) ( p < 0.01); a significant decrease in RER ( p < 0.01) and no change in SL and SPM ( p > 0.05) across the measured timepoints. F and Cr accounted for 61% of the variance in elapsed finish time ( $$R_{{{\text{adj}}}}^{{2}}$$ R adj 2 = 0.607, p < 0.01). Conclusion A treadmill ultramarathon elicits significant changes in metabolic variables, running energetics and spatiotemporal gait parameters. With F and Cr explaining 61% of variance in finish time. Therefore, those able to maintain a higher F , while adopting strategies to minimise an increase in Cr may be best placed to maximise ultramarathon performance.